Pelestarian Kampung Baduy Untuk Tujuan Wisata - Hartojo, Peni J; Pare Eni, Sri; Sudarwani, M Maria (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2025)
In this thesis, the object of cultural tourism in Lebak Regency with the capital city of Rangkasbitun is taken, with the title Preservation of Baduy village for tourism purposes. The Baduy tribe as a tribe that has a strong tradition of the village, house building/residential community. This research aims to find out the efforts that need to be made to preserve Baduy House as a traditional cultural tourism object. The condition of Baduy community and environment and how they utilize it wisely. The basic method used is survey method. The research was conducted in Kanekes Village, Leuwidamar District, Lebak Regency. Banten Province. The collected data, both primary and secondary data, were then analyzed by qualitative and quantitative descriptive analysis. The conclusion of this research is that Inner Baduy Village is the residence of Baduy tribe who still maintain the tradition of their ancestors so firmly. While in Outer Baduy Village, the modern influence has begun to be seen, with the presence of household appliances made of glass, metal, although it is still well preserved. Both have uniqueness and beauty that cannot be doubted